Heutagogical Approaches in the Merdeka Curriculum: Enhancing Autonomous Student Engagement - Subiyantoro, Singgih; Putra, Hamda Kharisma; Ismail; Mahendra, Moefty; Montle, Edward (Edutech Publishing Media, 2024)
The transition to the Merdeka Curriculum in Indonesia, emphasizing student autonomy and flexible learning pathways, presents an opportunity to explore heutagogical approaches in enhancing autonomous student engagement. This study aimed to investigate the effectiveness of heutagogy in promoting self-determined learning among students within this curriculum framework. Utilizing a mixed-methods approach, data were collected through surveys and interviews with students and educators, as well as classroom observations. The results indicated that students engaged in heutagogical practices exhibited higher levels of motivation, self-efficacy, and critical thinking skills, with 75 percent reporting increased confidence in managing their learning. Additionally, educators observed improved student participation and collaboration. The main conclusion is that heutagogical approaches significantly contribute to fostering autonomous learning environments, aligning with the goals of the Merdeka Curriculum. This research contributes to the educational field by providing empirical evidence supporting the implementation of heutagogy in national curricula, offering practical insights for educators and policymakers aiming to enhance student engagement and self-directed learning.